Analysis of Waiting Time for Filing Prescriptions in Hospital Pharmacy - Fauzia, Ulfa; Setiawati, Elsa P.; Surahman, Emma S. (Pharmacology and Clinical Pharmacy Research)
Patient waiting time for healthcare services is identified by the World Health Organization (WHO) as one of the key measurements of a responsive health system. Waiting time for filing prescription can influence patient satisfaction on hospital pharmacy service. This study was conducted to analyze current condition of waiting time for filing precription and related parameters. This study was prospective cross-sectional study conducted for 10 days at a hospital pharmacy, in Indramayu, Indonesia. Data regarding distribution of patients flow was obtained. Statistical analysis was performed using Kolmogorov-Smirnov. We observed that this hospital uses single queue channel-single phase model in three counters, i.e., public health insurance (PHI), private/general, government insurance (GI). The rate of patients visit was (λ) 9.40 and the rate of service was (µ) 1.26 in PHI. In private/general counter, the rate of patients visit was (λ) 5.03 and the rate of service was (µ) 4.08. The rate of patients visit was (λ) 4.85 and the rate of service was (µ) 5.85 in GI. Data indicated that there was excessive work loads. Thus, several strategies should be performed to decrease waiting time, e.g., the use of computer-based queuing system and the improvement of quality and quantity of human resources in the hospital pharmacy.Keywords: waiting time, outpatient, queueing theory